Examining the motivations of youth football athletes on sport continuation - Oronce, Sophia Liane Y. 2000-
Various studies have been conducted that illustrate the strong influence of the motivations of an athlete on their continued participation in a sport. Furthermore, the satisfaction of the basic psychological needs has been shown to greatly contribute to the intrinsic motivation of an athlete to play a sport. With the growing popularity of football in the Philippines, it is important to determine the factors that lead youth athletes to choose to play the sport and pursue their football careers. Data was collected through focus group discussions with twelve children participants from the Aspire Football Academy. The study aimed to examine their motivations in choosing to play football, the satisfaction of their basic psychological needs while playing and their reasons why they want to continue their involvement with the sport. The results of the study showed that then- motivations in playing the sport mainly come from their interest in football and the enjoyment that they gain while playing. It also showed that their basic psychological needs are satisfied while playing football. Lastly, their reasons for continuing to play football show a natural interest to pursue their football careers. With these findings, it hopes that football clubs and academies can introduce more strategies to attract children to play football by emphasizing the enjoyment that they can experience and the benefits that they can gain by playing.